ANALISIS REAKSI INVESTOR TERHADAP PENGUMUMAN RIGHT ISSUE DI BURSA EFEK JAKARTA (Suatu Pengamatan pada Return, Abnormal Return, Aktivitas Volume Perdagangan dan Bid-Ask Spread Saham) - SRI DEWI YUSUF; ATIM - DJAZULI; H.M. HARRY - SUSANTO (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT Development of stock market activity, which grows very fast lead to significant changes on the demand of information quality. To make the rational investor decision making, it is needed a relevant information in order to identify any work of the company. Event study is a study which analyze any market reactions toward an event which the information is published as announcement. Right issue announcement can affect market, it is depent on the existence of the content of the information in the right issue announcement above. If the right issue announcement contains some information so the market will react and the market won’t react if no information. The research sample is determined by a purposive sampling method, and there are 17 companies which announce right issue between 2000-2003. Statistical experiment used is T-test experiment (paired two samples for means). The Observation period which is done in 11 day, consist of 5 day before, 1 day in the moment, and 5 day after the announce right issue. Results show that there is a significant difference between return and abnormal return in the period of between at the moment, and after the announce right issue. The result in the before-after announce right issue period shows that there is no significant difference. The result in the variable activity of stock’s trade volume shows that there is signification difference in the before-at the moment and after period, but in the result of before-after period show that there is no significant difference there. And the result of bid-ask spread variable shows that there is no significant different in the before-at the moment and after period of announce right issue, but in the before-after period the result shows that there is no significant different there. And the result of bid-ask spread variable shows that there is no significant different in the before-at the moment and after period of announce right issue, but in the before-after period the result shows that there is significant different there. Cumulatively, this research gives a conclusion that announcement right issue have no information contents positive so that the market in general give no reaction. Keywords: Right Issue announcement, Return, Abnormal Return, TVA, Bid-Ask Spread